Study of diabetic ulcer with surgical complications of diabetes, their outcome and management modalities in 72 cases studied in Navi Mumbai - Shaikh, Tanveer Parvez; Lal, Vikash; Narayan, Pranav; Sinha, Subha; Deolekar, Sandesh (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes and its long term major complications include septic, vascular (either micro vascular or macro vascular) and neuropathic lesions which affect the various anatomical regions of the body. Majority of admissions to surgical wards is due to these surgical complications of diabetes. So this is a study of these surgical complications of diabetes, their outcome and management modalities. Methods: This “Clinical study of surgical complications of diabetes” consists of a study of minimum of 50 or more cases admitted to surgical wards of Dr. D Y Patil hospital & research centre, from June 2010 to Oct 2012. A series of 72 cases were compiled for this study during this period. This study is to know more about the mode of presentation, clinical features and outcome of management of surgical complication of diabetes mellitus. Results:In present study, 30 cases were conservatively managed with meticulous debridement. 13 cases underwent incision & drainage and came for regular follow-up. 10 cases underwent disarticulation of toes. Four patients underwent below knee amputations whereas 8 patients underwent above knee amputations and 7 patients needed split skin grafting for covering of raw area. Conclusions:Patients on irregular medication usually from age group 51-60 majorly male who undergo trauma (lower limb >>upper limb) are prone to diabetic ulcer complication. Mortality in these patients is due to complications. Conservative management is the mainstay of this condition followed by I & D and finally amputation.